BIMBINGAN PENGEMBANGAN WAWASAN KARIR DI SEKOLAH DASAR NEGERI AFALSIA - Endang Serang; Dorkas Penau, Yessy Mata, Efelin Kela Mau, Petrus Mau Tellu Dony, Yermia S Wabang (CV. ADIBA AISHA AMIRA (ADISAM PUBLISHER), 2025)
The purpose of this study was to determine the form of career insight development guidance at GMIT Afalsia Elementary School, Morba Village, Alor Barat Daya District, Alor Regency. The research technique used in this study was descriptive qualitative, with interviews with the fifth-grade homeroom teacher, Mrs. Eneni Melinda Hingkoli, S.Pd., at Afalsia State Elementary School, Alor Barat Daya District, Alor Regency. The results of this study indicate that the homeroom teacher has provided career insight development guidance services in the classroom, and students have also received career insight development guidance services at Afalsia State Elementary School, grade 5.